Layered mission control architecture and strategy for crawling underwater cleaning robot. (2015) - Albitar, Houssam; Dandan, Kinan; Ananiev, Anani; Kalaykov, Ivan
This paper presents the mechanical design and the control system architecture of an underwater robot, developed for bio-fouling cleaning surfaces. The robotic system presented here has been designed to improve the productivity, reduce the environmental impacts, and exclude the hazards for the operators. The control system has a layered structure which is distributed into two blocks: cleaning robot, and on-board base station connected with power and control cables and a water hose, to facilitate different modes of operations and to increase the system reliability. A low level control has been implemented on the robotic platform. The onboard station designed to be in different layers of the control system: manual, semiautonomous and autonomous modes. A scaled prototype has been implemented and tested to prove the concept, and to make certain that the mechanical design and the chosen control system are perfectly suited to the main functions of the robotic system.